PRICE EARNING RATIO (PER) DAN NILAI WAJAR SAHAM: EVALUASI KRITIS DALAM INVESTASI (Studi Pada Saham PT Kalbe Farma Tbk, Periode 2019-2023) - Marli Marli; Widanarni Pujiastuti (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to evaluate the fair value of PT Kalbe Farma Tbk (KLBF) shares using the Price Earning Ratio (PER) approach as one of the stock valuation methods commonly used in investment analysis. This method is carried out by calculating the estimated intrinsic value of shares based on the multiplication of the estimated Earnings Per Share (EPS) and the average PER industry. The data used include EPS, profit growth rate, and stock market price during the period 2019 to 2023. The results of the analysis show that for five consecutive years, KLBF shares have been undervalued, where the intrinsic value of the shares is higher than the actual market price. This finding indicates that KLBF shares have the potential for price appreciation in the future, along with the stability of the company's financial performance as reflected in EPS growth and consistent Return on Equity (ROE).